Writing about the Practices of Teachers in Training. The report as Mediator in Academic Education - Pereira Costa, Rogério (2020)
The purpose of this paper is to analyze how knowledge is constructed and how it is described in the courses of supervised professional practicum. To achieve this, based on undergraduate students’ practicum reports from various universities, we identified two fundamental questions in the process producing and receiving knowledge by means of writing, which were i) what is the description of the voices in the practicum reports like? and ii) how does time management happen in the reports? Based on the linguistic analysis of the students’ written products, the emphasis is on the theoretical construction of the pre-service teachers since the supervised practicum requires a more rigorous look. Practicing students’ writing provides key elements in the production of knowledge, showing that the genre of practicum reports reflects a general format and theoretical superficiality.